PLGA-microspheres-carried circGMCL1 protects against Crohn’s colitis through alleviating NLRP3 inflammasome-induced pyroptosis by promoting autophagy - Jie Zhao; Ye Sun; Haojun Yang; Jun Qian; Yan Zhou; Yu Gong; Yi Dai; Yuwen Jiao; Weiming Zhu; Honggang Wang; Zhiliang Lin; Liming Tang (Cell Death and Disease, 2022)
Abstract This study aimed to at explore exploring the biological functions of dysregulated circRNA in Crohn’s disease (CD) pathogenesis, with the overarching goal of and providing potential novel therapeutic targets. CircRNA microarray and quantitative real time-polymerase chain reaction (qRT-PCR) analyses were performed to investigate and verify the candidate dysregulated circRNA. The Next, clinical, in vivo, and in vitro studies were performed to investigate explore the biological function and mechanisms of the candidate circRNA in CD. The therapeutic effect of poly (lactic-co-glycolic acid)-microspheres (PLGA MSs)-carried oe-circGMCL1 in experimental colitis models of IL-10 knock-out mice was assessed. CircGMCL1 was identified as the candidate circRNA by microarray and qRT-PCR analyses. Results showed that circGMCL1 expression was negatively correlated with CD-associated inflammatory indices, suggesting that it is a CD-associated circRNA. Microarray and bioinformatics analyses identified miR-124-3p and Annexin 7 (ANXA7) as its downstream mechanisms. The in vitro studies revealed that circGMCL1 mediates its effects on autophagy and NLRP3 inflammasome-mediated pyroptosis in epithelial cells through the ceRNA network. Moreover, the in vivo studies identified the therapeutic effect of PLGA MSs-carried oe-circGMCL1 in experimental colitis models. This study suggests that circGMCL1 protects intestinal barrier function against Crohn’s colitis through alleviating NLRP3 inflammasome-mediated epithelial pyroptosis by promoting autophagy through regulating ANXA7 via sponging miR-124-3p. Therefore, circGMCL1 can serve as a potential biological therapeutic target for Crohn’s colitis.